Ball milling: A top down facile approach to synthesize AgInSe2 nanostructures - Pathak, Dinesh; Wágner, Tomáš; Šubrt, Jan; KupčíK, Jaroslav (University of Pardubice, 2014)
A quantum dot solar cell is an emerging field in solar cell research that uses quantum dots as the photovoltaic material. Quantum dots have band gaps that are tunable across a wide range of energy levels by changing the quantum dot size. The embedment of different sized dots within absorbing layer encourages harnessing of the maximum spectrum energy. Also other effects like very high surface to volume ratio, Quantum Transport make them attractive for future devices. For an attempt of AIS quantum dots (QDs), AIS nanoparticles with tetragonally distorted phase were prepared by mechanically alloying the synthesized bulk AIS powder at room temperature in a planetary ball mill under Ar. Nanoparticles are formed with range -10 nm in size. These ball-milled nanoparticles contain different shapes, and the Rietveld analysis of X-ray powder diffraction data reveals their detailed structural features. High resolution transmission electron microscope (HRTEM) images also detect the presence of the tetragonal phase in ball-milled samples. Peak Broadening (FWHM), which is the main characteristics of decrease in size, is observed. XRD data reveals the downscaling of crystallite from 103 nm to 7 nm, also tetragonally distorted structure of the system was not disturbed by milling. The DSC study also reveals the phase evolution and crystallization kinetics. Bulk samples show endo melting peak at 134 °C and 220 °C. Cooling-crystallization complexity of the peak/peaks signifies crystallization from melt was heterogeneous nucleation and crystallization from multiple types of centers. Unlike this, milled samples show two crystallization effects at approx. 135 °C and 380 °C. Optical properties were investigated to find band edges, and suggest it around 1.3 eV which is encouraging for photovoltaic applications.